DEVELOPMENT OF OPERATING SYSTEMS AND THEIR IMPACTS FOR THE FORMATION OF SCHOOLS OF FUTURE IT SPECIALISTS - YUSKOVYCH-ZHUKOVSKA, VALENTYNA; LOTIUK, YURII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The dynamic development of the digital society is characterized by the global digitization of all spheres of life and provides access to global information and communication technologies. Operating systems exist as a basic part of the digital society, providing comprehensive management of software and hardware. Mastering the basic principles of the latest information technologies and the formation of professional skills is a valuable component for training future IT specialists: software and hardware developers, DevOps Engineers, testers, providing the necessary foundation for a successful IT career. The issues of choosing the most effective OS for a particular IT project and guaranteeing cyber security in the OS are becoming relevant for IT specialists. A key aspect of the development of operating systems is their protection against cyber attacks. Virtually all companies use network resources and cloud technologies, so there is a growing need for effective means of detecting and preventing vulnerabilities.  The rapid development of artificial intelligence opens up new perspectives in the field of OS development and cyber protection. In the future, artificial intelligence technologies will be able to continuously monitor, detect, analyze and neutralize potential threats faster than IT professionals. Automated tools for detecting vulnerabilities already allow you to quickly identify vulnerabilities in the network infrastructure and take measures to eliminate them. This theoretical study on the development of modern operating systems ensures the formation of hard skills in the training of qualified IT specialists who are able to ensure the setting of OS security parameters to protect against unauthorized access. As part of the conducted theoretical research, an electronic laboratory workshop "Operating Systems" was developed in the cloud environment. The created workshop using a virtual environment, cloud services and artificial intelligence technologies will bring the training of IT specialists to a new, higher level.
Keywords: operating systems; cloud environment; hard skills; IT specialists; cyber protection